3. Genuistico - Evolving Aspects of Sonata II for Violin and Piano, OP. 19, No. 3, by Constantin Silvestri - Melnic Victoria; Florea Augustina (Sciendo, 2022)
The article addresses the problem of investigating the evolutionary paradigm of the sonata for violin and piano in the Romanian compositional creation of the first half of the twentieth century, analyzing the work of the famous representative of the pleiad of Romanian composers of the Postenescu generation, European personality - Constantin Silvestri. His creation - Sonata II for violin and piano (1939), composed at the end of the interwar period, at the confluence of the '30s and' 40s, revealing a complex emotional and imagistic spectrum, contrasting, generated by the striking antagonism between aspirations to the ideal and ruin of illusions, allegorically transfigures the incandescent atmosphere around World War II. The language of the work presents a stylistic symbiosis distinct from heterogeneous elements: romantic, expressionist, as well as folk resonance.